Cerebral Embolism Associated with Left Atrial Myxoma That Was Treated with Thrombolytic Therapy - Kohno, Naoto (S. Karger AG, 2012)
We present a case of cerebral embolism associated with a left atrial myxoma that was treated with intravenous thrombolytic therapy. A 79-year-old right-handed man with no history of neurological or psychiatric illnesses was referred to our hospital because of confusion. He had been self-supported in the activity of daily living and could enjoy gardening until just before his admission. He had aphasia, left conjugate deviation, right hemiparesis, and right pathological reflexes. His NIHSS score was 24. Cranial DWI showed hyperintense lesions in the left middle cerebral artery territory, and MRA revealed left middle cerebral artery occlusion. We started treatment with the recombinant tissue plasminogen activator alteplase intravenously 3 h after the onset. However, the therapy was ineffective, and the NIHSS score was 25 on the second day. A transthoracic echocardiogram and heart MRI showed a left atrial myxoma. However, surgery was contraindicated because of the patient's poor general condition. Although intravenous recombinant tissue plasminogen activator is a reasonable treatment for stroke patients, even with a cardiac myxoma, we cannot always expect good effects, especially if the emboli are parts of the tumor itself. In this case, we could not perform an endovascular mechanical embolectomy; however, we speculate that mechanical embolus retrieval in cerebral ischemia might be effective in such cases.